Assessment Model and Virtual Simulation for Fatigue Damage Evolution of Asphalt Mortar and Mixture - Danhua Wang; Xunhao Ding; Linhao Gu; Tao Ma (Advances in Materials Science and Engineering)
Focused on the fatigue performance of the asphalt mortar, this study proposed an assessment model for fatigue damage evolution based on the continuum mechanics. From the perspective of the material scale rather than the macrostructure, the proposed damage model was set by concentrating on the stress-strain state of a tiny point which could characterize the material performance accurately. By the mechanical formula derivation and based on the four-point bending fatigue tests, the damage evolution law was determined and then the proposed model was verified. Based on the finite element method (FEM), a commercial software named ABAQUS was utilized to develop the random mixtures consisting of coarse aggregates, mortar, and voids. Eventually, combined with the damage model and virtual simulation of bending tests, the factors influencing the fatigue resistance of the whole asphalt mixtures were analyzed further.